Also in Crayfish: How Phytase Inclusion Avoids Phytic Acid Effects on Hepatopancreas Enzymes of Redclaw Cherax quadricarinatus - Casaretto, Matías Ezequiel (2023)
This work aimed to evaluate the effects of dietary phytic acid on the enzymatic activities of the hepatopancreas of the redclaw crayfish, Cherax quadricarinatus. For this purpose, a completely randomized in vitro trial was conducted with three phytic acid levels (0.56, 1.68, and 2.80%) and three phytase doses (0, 250, and 500 PU/kg DM). Solubilized protein, reducing sugars, and soluble phosphorus showed significant responses to the interaction between phytic acid and phytase . Only the main effects were detected on the released amino acids, in keeping with the main effects of alkaline protease activity, which are negatively affected by phytic acid and improved by phytase inclusion . Differences in released reducing sugars were attributed to a reduction in amylase activity by increased levels of phytic acid and not to cellulase activity, where only a negative trend of phytic acid was found . Phytic acid depresses calcium availability, which would explain the decrease in amylase activity. A 500 PU/kg DM dose improved amino acid, reduced sugars, and phosphorus release. These in vitro results might have in vivo implications for the digestibility of proteins, minerals, and energy. Further investigations are required to determine the chelated calcium effect on redclaw amylase activity, molting, and survival.